Distribution of Gypsiferous Soil Using Geoinformatics Techniques for Some Aridisols in Garmian, Kurdistan Region-Iraq - Azeez, Salim Neimat; Rahimi, Iraj (Kurdistan Journal of Applied Research, 2017)
The paper deals with techniques of image classification developed to distinguish gypsiferous soils, using the integration of field observation and remote sensing and more specific Landsat/ETM imagery. A Landsat image was assembled and used in this study. The image was acquired by the ETM/Landsat 7 sensor, which was acquired on August, 2012.Two main data have been used in this research, I) Field and II) Satellite data. The amount of gypsum is different from location to other, may be due to the parent material of some locations of the study area which is rich with gypsum minerals, and there is evidence of Gypsic indopedon horizon. The results indicated that the amount of organic matter decreases with increasing the amount of gypsum. In general, the study area is rich with total lime. These results reflect the effect of decalcification and calcification processes caused the formation of illuvial subsurface (calcic) horizon in some location of the study area.The pH values were around neutral to slightly alkaline due to the effect of calcareous parent material and type of climatic conditions. The low ECe values indicate that the soil was non-saline reflected by low values of ECe. The soil classes of the study area are belonging to Haplogypsids, Haplocalcids, Haplocambids, Calciargids and Haplargids. Two maps were prepared to show the distribution of gypsiferous in the study area, the first one is map which shows the output of supervised classification and maximum- like hood for specific, and the second is the thermal-based classification. Thermal-based map could predict the gypsiferous area in a better way, than the classification based only on spectral properties of non-thermal bands.